Galectins expressed differently in genetically susceptible C57BL/6 and resistant BALB/c mice during acute ocular Toxoplasma gondii infection. Issue 8 (9th March 2017) - CHEN, S.-J.; ZHANG, Y.-X.; HUANG, S.-G.; LU, F.-L.
SUMMARY: Ocular toxoplasmosis (OT) caused by Toxoplasma gondii is a major cause of infectious uveitis, however little is known about its immunopathological mechanism. Susceptible C57BL/6 (B6) and resistant BALB/c mice were intravitreally infected with 500 tachyzoites of the RH strain of T. gondii . B6 mice showed more severe ocular pathology and higher parasite loads in the eyes. The levels of galectin (Gal)-9 and its receptors (Tim-3 and CD137), interferon (IFN)- γ, IL-6 and IL-10 were significantly higher in the eyes of B6 mice than those of BALB/c mice; however, the levels of IFN- α and - β were significantly decreased in the eyes and CLNs of B6 mice but significantly increased in BALB/c mice after infection. After blockage of galectin–receptor interactions by α -lactose, neither ocular immunopathology nor parasite loads were different from those of infected BALB/c mice without α -lactose treatment. Although the expressions of Gal-9/receptor were significantly increased in B6 mice and Gal-1 and -3 were upregulated in both strains of mice upon ocular T. gondii infection, blockage of galectins did not change the ocular pathogenesis of genetic resistant BALB/c mice. However, IFN- α and - β were differently expressed in B6 and BALB/c mice, suggesting that type I IFNs may play a protective role in experimental OT.